Climate change policy : what do the models tell us - Pindyck, Robert S. (2013)
Argues that the integrated assessement models (IAMs) that have been constructed and used to estimate the social cost of carbon (SCC) and evaluate alternative abatement policies are so deeply flawed that they are close to useless as tools for policy analysis.